Premedication with fentanyl-midazolam improves sevoflurane anesthesia for surgical intervention in laboratory mice - Lipiski, Miriam (Exp Biol Med (Maywood), 2017)
Balanced anesthesia allows for a reduced dosage of each component, while inducing general anesthesia of sufficient depth with potentially fewer side effects. Here, we compare two anesthetic protocols combining sevoflurane anesthesia with pre-medication (ketamine [K] or fentanyl-midazolam [FM]) to a sevoflurane monoanesthesia (S) concerning their ability to provide reliable anesthesia suitable for moderate surgery in laboratory mice. Twenty-one female C57BL/6J mice assigned randomly to one of three protocols underwent a 50-min anesthesia and a sham embryo transfer. Heart rate and core body temperature were continuously recorded by telemetry intra-operatively and for three days pre- and three days post-surgery. Intra-operative respiratory rate was determined by counting thorax movements. Body weight, food, and water intake were measured daily for three days pre- and three days post-surgery. The heart rate in the KS group remained at baseline level throughout the 50-min of anesthesia and surgery. FMS caused a lower heart rate and S alone caused a higher heart rate compared to baseline values. Intra-operative body temperature was at baseline levels in all groups. A decreased respiratory rate was observed in all groups compared to baseline values obtained from resting mice of the same strain, sex and age-distribution. Surgical stimuli induced no significant changes in heart rate and respiratory rate in the KS or FMS group but significant respiratory alteration in the S group compared to baseline values obtained 10 s before applying the stimulus. Post-operative heart rate was above baseline values in all groups; with a significant deviation in the S group. There were no changes in body weight, food, and water intake. In summary, FMS was superior to KS and S for moderate surgery in laboratory mice resulting in less inter-individual variability in response to painful stimuli. Fentanyl and midazolam reduced the depressant effect of sevoflurane on the respiratory rate and the negative post-anesthetic effects on the heart rate. IMPACT STATEMENT: With approximately 65 million animals used per year mice are still the most prevalent laboratory mammal species worldwide. In course of biomedical research projects approximately 40% of mice will undergo one or more short or long-term anesthesia. Sufficient anesthetic depth, cardiovascular stability, adequate analgesia, and short recovery times are essential requirements of anesthetic protocols to meet animal welfare. Anesthesia in mice and rats are only to be performed by personnel with appropriate basic training and experience. However, more and more adapted and advanced anesthetic protocols, required to answer very specific scientific questions, often exceed the skills acquired through basic training and present a major challenge to researchers. It is therefore of great importance to further develop and evaluate safe and reliable anesthetic protocols as presented in this study to provide new perspectives on this challenging problem.